Emergence and Development of Bullet Comments in China - Wang, Aiqing (Universitas Negeri Semarang, 2021)
Danmu denotes user-generated dynamic and contextualised comments scrolling across the screen. Owing to its resemblance to a bullet curtain, such a text-over-screen technology is referred to as ‘bullet comment/message’ or ‘barrage subtitling’. Since being adopted from Japan, danmu has expeditiously developed from a niche subcultural entity into a prominent property of Chinese online video culture. Danmu obtains popularity among young audiences, in that it establishes social media co-viewing, creates a sense of belonging, allows self-expression and facilitates social connectedness. Moreover, danmu enables creators to demonstrate a sense of existence, especially via informative, alerting and spoiler comments. The popularity of danmu in China is ascribed to diversified and concise literacy practice. More significantly, it is attributed to linguistic and cultural prerequisites: the Chinese written language is featured by a high information density and robust parafoveal preview effects; the Chinese culture is marked by a high level of polychronicity and collectivism, as well as conspicuous social and peer pressure.